Improvement and shelf life extension of fresh creams chocolate filling for Tolaal Enterprise - Mohamad, Nur Sadrina; Abdul Razak, Raihana; Harun, Sri Salawa Salawati; Karim, Roselina; Hussain, Norhayati (Program Pemindahan Ilmu - Kementerian Pendidikan Malaysia, 2014)
Tolaal Enterprise is facing problems associated with softening of chocolate fillings made from fruit purees, leading to a shorter shelf life (less than 2 weeks) of the product. Thus, this work aimed to transfer knowledge on improving the textural properties of mango and pineapple flavoured fresh cream fillings by using hydrocolloid which acts as a thickener in the filling formulations during chilled storage. Based on our findings, addition of xanthan gum at levels of 1.0% and 2.0% for mango and pineapple fresh cream fillings, respectively, was chosen as the best thickener to give a better and stable texture. In addition, no significant difference (p>0.05) in the overall acceptability of the taste of both filled mango and pineapple milk chocolates was detected. Therefore, through improvement of the textural quality of mango and pineapple fresh cream fillings, the company is able to produce milk chocolate of high quality with extended shelf life (i.e. 4 months) to meet the customers’ expectations and hence, to increase the profit of the company.